Hubungan Karakteristik Petugas dengan Kesesuaian Kode Diagnosis pada Rekam Medis Rawat Jalan dan Software INA CBGs di RS PKU Muhammadiyah Yogyakarta Unit I - Widayanti, Nurzara Anggar; , Ibnu Mardiyoko, SKM. MM; , Yuli Kusumawati, SKM. M.Kes (Epid) (2016)
According to regulation No. 24 in 2011 about BPJS and No. 40 in 2004 about SJSN, giving diagnose's code is important. Diagnose's code should complete and accurate accordance by ICD-10. Characteristics of the person can affect their behavior in the work place. Therefore, individual's characteristics (gender, employment's status, and length of employment) can be affecting their performance. The purpose of this researches is to know the relation of medical record practitioner's characteristic with conformity of diagnose's code in outpatient's medical record and INA CBGs's software in RS PKU Muhammadiyah Yogyakarta Unit I. This study used analytic observational research with cross sectional study design. The population of research is outpatients's medical record in January 2016 (3006 medical record). The sample in this study is 188 outpatient's medical record using techniques of sistematic sampling. The analysis showed that diagnose's code of outpatient's medical record and INA-CBGs' software as many as 41 files (22%) not conform. There is a correlation between gender (0,003), employment status (0,0001), and length of employment (0,0001) with conformity of diagnose's code in outpatient's medical record and INA CBGS's software in RS PKU Muhammadiyah Yogyakarta Unit I.